Slavonic Apocrypha: The Main Problems with Their Textual History (a Philological Perspective) - Navtanovich, Liudmila (2018)
On one hand, Slavonic Apocrypha share the same characteristics with the other Old Slavonic Literature. But on the other, they had their own peculiarities in terms of the process of translating, editing and copying the text during its existence in Slavonic version. Consequently, while some of the problems of their textual history might be common to the rest of the Slavonic Translated Literature, others are peculiar to themselves alone. This paper presents certain problems that need to be resolved when reconstructing the textual history of a Slavonic Apocryphon. The resulting analysis is based on research into different Slavonic Apocrypha, among them the enigmatic 2 Enoch.
Keywords: Old Testament Pseudepigrapha -- Slavonic Apocrypha -- textual history -- 2 Enoch